Flood Management and Geoinformation Support within the Emergency Cycle (EU Example) - Kubíček, Petr; Muličková, Eva; Konečný, Milan; Kučerová, Jitka (Environmental Software Systems. Frameworks of eEnvironment, 2011)
Paper describes the state-of-the-art of flood management both in the Czech Republic and in the broader framework of EU. Special focus is given to geoinformation and cartographic issues within consecutive parts of emergency management cycle used in European Union countries (prevention, preparation, response, and recovery phases). For each phase an adaptive mapping solution is outlined. The principles of adaptive cartography and its applications are described.